Perkembangan HAM Di Indonesia Dan Problematikanya - Widyawati Boediningsih; Novi Prameswari Regina Dermawan (Education : Jurnal Sosial Humaniora dan Pendidikan, 2023)
Human rights (HR) in Indonesia have been regulated and protected by Indonesian laws. However, the implementation of HR in Indonesia still faces various problems, such as HR violations committed by individuals, limited freedom, and inadequate HR enforcement. The history of HR enforcement in Indonesia is lengthy, even since the early independence era. However, the legal politics of HR in Indonesia still needs to be improved so that the rights of every Indonesian citizen can be implemented freely and optimally. Therefore, there is a need for efforts from the government and society to increase awareness of the importance of HR and improve the implementation of HR in Indonesia.